The Math and Science Engagement Scales: Scale development, validation, and psychometric properties - Wang, Ming-Te; Fredricks, Jennifer A.; Ye, Feifei; Hofkens, Tara L.; Linn, Jacqueline Schall (Learning and instruction, 2016)
There is an urgent need to develop appropriate instruments to measure student engagement in math and science for the fields of research and practice. The present study developed and validated student- and teacher-report survey measures of student engagement in math and science. The measures are built around a multidimensional perspective of engagement by using a bifactor modeling approach. The sample was recruited from an ethnically and socioeconomically diverse middle and high school student population in the United States. The findings confirmed that student engagement is comprised of multiple related yet distinct dimensions, with evidence to support a bifactor structural model. There was also empirical evidence supporting measurement invariance and predictive validity. The results demonstrate the soundness of the psychometric properties of the Math and Science Engagement Scales. •Developing appropriate instruments to measure student engagement in math and science is needed.•Student engagement is a multidimensional construct, including behavioral, emotional, cognitive, and social components.•The use of multiple informants to assess student engagement provides a more comprehensive perspective.•Math and science engagement predicted academic performance and career aspirations.